Infant Mortality is Higher in Rural Counties. Issue 2 (March 2021) - Beal, Judy A.
Abstract : Access to health care services is limited in rural areas of the United States. Two recent studies highlight the health inequities experienced by this population and subsequent effects on infant morbidity and mortality. Our pediatric nursing expert, Dr. Beal, explains the findings and what pediatric nurses can do to promote the health and wellbeing of babies and children in rural United States.